2022
DOI: 10.1186/s12888-022-04022-x
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment, homelessness, and other societal outcomes in patients with schizophrenia: a real-world retrospective cohort study of the United States Veterans Health Administration database

Abstract: Background The burden associated with schizophrenia is substantial. Impacts on the individual, healthcare system, and society may be particularly striking within the veteran population due to the presence of physical and mental health comorbidities. Disease burden is also influenced by a complex interplay between social determinants of health and health disparities. The objective of the current study was to compare non-healthcare societal outcomes between veterans with and without schizophrenia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 53 publications
0
8
0
1
Order By: Relevance
“…A higher percentage of participants with schizophrenia were unemployed or had nonregular employment, had lower household incomes, were less likely to be married, and lived with their parents than participants without schizophrenia. Despite evidence indicating that individuals diagnosed with schizophrenia are more likely to be unemployed [22] or have lower income [73] than the general population, there is a paucity of research investigating whether they are more likely to be unmarried or residing with their parents. However, our finding is consistent with a previous Japanese study, which also found a high prevalence of unmarried, unemployed, and low household income among individuals with schizophrenia [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher percentage of participants with schizophrenia were unemployed or had nonregular employment, had lower household incomes, were less likely to be married, and lived with their parents than participants without schizophrenia. Despite evidence indicating that individuals diagnosed with schizophrenia are more likely to be unemployed [22] or have lower income [73] than the general population, there is a paucity of research investigating whether they are more likely to be unmarried or residing with their parents. However, our finding is consistent with a previous Japanese study, which also found a high prevalence of unmarried, unemployed, and low household income among individuals with schizophrenia [15].…”
Section: Discussionmentioning
confidence: 99%
“…Depression in individuals with schizophrenia can exacerbate the symptoms of schizophrenia, worsen the quality of life, and increase the risk of suicide [20]. Unemployment in individuals with schizophrenia can reduce the quality of life and place an extended burden on social support and disability services [21][22][23]. Addressing physical, psychiatric, and social comorbidities in primary care in the community is crucial in improving the health outcomes of individuals with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on the effect of unemployment on physical and mental wellbeing have shown an increased risk of psychiatric disorders in unemployed persons, [33][34][35] suggesting a possible causal explanation for the increased risk of unemployment in the PCM group. As unemployment to some extent increases both the chances of illness and mortality, [36][37][38][39] this could pose an additional risk for the group of patients with both PCM and HS. Furthermore, unemployment serves as an additional factor in impairment of quality of life in patients with HS.…”
Section: Perspectivesmentioning
confidence: 99%
“…Patients with SMI are likely to experience disadvantages of low socioeconomic status, low educational attainment, unemployment, social isolation, homelessness, criminal justice involvement, and substance use disorder, all of which are associated with an increased risk of developing cardiometabolic conditions [23][24][25][26]. They may also be more likely to live in congregate settings, with limited control of menu planning and choice of healthy foods.…”
Section: Patient-level Barriersmentioning
confidence: 99%